Exposure from occupational versus other sources. - Fishbein, L. (Scandinavian Journal of Work, Environment & Health, 1992)
There is an increasing need to consider the various routes of exposure to individuals in occupational settings, as well as the exposure of the general public to a broad spectrum of carcinogens. The need to consider indoor environments is increasingly recognized in light of the amount of time spent indoors by a large majority of the population and the recognition that levels of certain toxicants are higher indoors than outdoors. This overview highlights (i) a general comparison of exposure to indoor and outdoor levels of 12 volatile organic compounds and (ii) the exposure of workers and the general public to benzene, 1,3-butadiene, formaldehyde, styrene, tetrachloroethylene, phthalate esters, polychlorinated dibenzofurans, radon, and electromagnetic fields.